Brazilian trade policy: a successful model impacting the role of developing countries withing the World Trade Organization - Santos Navarro, Johanna (AUC Knowledge Fountain, 2013)
Our world economy is constantly changing and within the process, new market players have started emerging and transforming international trade relations. Furthermore, multilateral organizations have become more important than ever for developed and developing countries as common forums to discuss international treaties and to resolve trade disputes. Within this context, Brazil in particular has experienced a positive transformation of its economy during the last 40 years, and has now become a new economic power guiding emerging economies in their strategic use of the international trade legal system. This study analyzes three particular issues that are common to developing countries within the World Trade Organization (WTO): agricultural subsidies, anti-dumping, and the TRIPS Agreement, with a particular focus on the negotiation process with developed countries and the various outcomes obtained. The study illustrates Brazil’s influence on the role of the developing countries in light of each of the common issues examined, by presenting examples of trade disputes taken before the WTO where Brazil has had direct participation and obtained a positive result. This paper argues that the WTO continues to be an agent for economic development given its platform to provide the third world with the opportunity to both discuss trade agreements at an international level, and to participate in a neutral system for trade dispute settlement. In addition, this paper recognizes that the WTO remains a strategic option to influence global international trade as with the example of Brazil. While this study highlights the fact that Brazil has achieved particular milestones on its own and as a result has helped develop the role of emerging economies within the international trade arena, it also emphasizes the need for each of the developing countries to confront their own specific challenges in order to realize economic development, as Brazil did. Brazil has been and can be a great example for the developing world within the WTO framework, but it certainly is not the only solution to all developing world problems.